Ready or not? - Chen, Kirmaine Yee Jing (Nanyang Technological University, 2020)
Ready or Not? is a communication campaign aimed at encouraging retirement well-being planning in Singapore. Targeted at 50 to 65 year olds, Ready or Not? sought to encourage planning for retirement in ways beyond the financials, by equipping them with information about retirement planning resources. Planning for retirement well-being can help manage retirement transition. Yet, it is a behaviour that few pre-retirees in Singapore engage in. Qualitative and quantitative research informed us of the need to make retirement planning resources more accessible and to increase the ability of pre-retirees to find activities they can realistically engage in during retirement. These insights help shape the campaign strategy which was executed through two channels, directly to the target audience and through human resources managers of various employers. The paper concludes with an evaluation of the campaign’s effectiveness in achieving our objectives based on post-campaign research. This consisted of interviews with human resource managers and with participants of the campaign, as well as a post-campaign survey. The campaign reached over 1,600 pre-retirees and overall feedback from both campaign partners and participants was positive. Campaign evaluation also shows that those exposed to the campaign were better informed on how to start preparing for their retirement well-being than those who were not. Finally, the paper contains limitations and future recommendations for the campaign, as well as suggestions for possible sustainability initiatives.